Making Virgin Coconut Oil (VCO) with Fermentation Process Using Fermipan and Addition of Pineapple Extract - Nurma W, Kindriari; Wilya VP, Robet; Perdana, Dean (Future Science)
Virgin coconut oil (VCO) is a form of processed coconut meat that has recently been produced for commercial use. Virgin coconut oil or pure coconut oil is the result of processed coconut that is free of trans-fatty acid (TFA) or trans-fatty acids that are easily digested and oxidized by the body to prevent accumulation in the body. Trans fatty acids can occur due to the hydrogenation process, so as not to undergo the hydrogenation process, the extraction of coconut oil is carried out by the fermentation process. This research was conducted by the Fermentation method using Fermipan as a microbe and the addition of the bromelin enzyme from pineapple extracts. The variables in this study were 100 ml of coconut milk volume, pH 4, and fermipan weight 0.2 gr. The variables implemented were pineapple extract volume (20, 25, 30, 35, 40) ml, fermentation time (18, 24, 30, 36, 42) hours. Analysis of VCO results compared with VCO SNI, namely the content of water content, free fatty acid numbers, saponification numbers, and iodine numbers. Optimum VCO results were obtained at 30 hours fermentation time and 30 ml pineapple extract which produced 35 ml rendamen, water content 0.08, free fatty acid numbers 0.1, saponification number 72.9, and Iodine number 26.65.